Challenges of Whale Watching and Swim With Dolphins in Mexico - Jorge Urbán, R.; Viloria-Gómora, Lorena (Frontiers in Marine Science, 2021)
Mexico is one of the top ten whale-watching destinations in the world. The target species for "whale watching" (WW) are the gray whale, blue whale, humpback whale, and fin whale; the target species for "swim with dolphins" (SWD) are the bottlenose dolphin, spotted dolphin, spinner dolphin, and killer whale. WW has an increment of 666% income, 94% of trips, and 51% in the jobs generated in the last 11 years. Although Mexican legislation with whale watching is good, the great challenge is applying normativity in the field. There is a significant difference in the surveillance where the WW is inside a Marine Protected Area (MPA) or not. In the case of the gray whales, the Biosphere Reserve El Vizcaino is an example of a good WW in the world. The WW on blue whales is in another MPA, the National Park Bahía de Loreto, and is another example of good practices. Puerto Vallarta, Jal., and Los Cabos, BCS, are not protected. The principal problems are with the vessels without a permit, sport fishing boats, particular ships, and sea motorcycles which do not respect the WW guidelines. The Mexican normativity does not regulate SWD activities. It is necessary to create an Official Mexican Standard with the SWD's normativity and guidelines in Mexico. Another challenge is promoting the WW and SWD good practices to involve the local communities in these tourism activities to include them in the permits granted, jobs generated, and benefits of the increasing income.